Pengaruh Komposisi Media Tanam dan Frekuensi Penyiraman Air terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Maria Odilia Bou Seran; Maria Angelina Tuas; Magdalena Sunarty Pareira; Asep Ikhsan Gumelar (Fakultas Pertanian, Universitas Timor, 2022)
The composition of the growing media and the frequency of watering can be used as a way to increase the productivity of pakcoy plants. A study was conducted to determine the effect of planting media composition and frequency of watering on the growth and yield of pakcoy (Brassica Rapa L.) on entisol soil in the greenhouse of the Faculty of Agriculture, the University of Timor in April to August 2021 using a factorial completely randomized design consisting of two factors which were repeated 4 times. The first factor consisted of 3 levels, namely soil without biochar compost (K0), 50% biochar compost + 50% entisol soil, (K1), and 75% biochar compost + 25% entisol soil (K2). The second factor consisted of 3 levels, namely the frequency of routine watering in the morning and evening (F0), the frequency of watering every 2 days in the morning and evening (F1), watering every 4 days in the morning and evening (F2). The results showed that the treatment of planting media and the frequency of watering had a significant effect on each parameter and positively interacted with the parameters of the degree of soil acidity. Treatment of planting media dose of 50% biochar compost + 50% entisol soil was the best treatment in increasing the growth and yield of pakcoy plants. The frequency of watering for 4 days in the morning and afternoon was the best treatment in increasing the growth and yield of pakcoy plants.